Embedded system based driver drowsiness detection system - Islam S.Z.; Mohd Ali M.A.; Bin Jidin R.; Islam S.Z. (2023)
This paper presents a System-on-Chip (SoC) visual-based driver drowsiness detection system. The system is able to promptly detect the onset of driver drowsiness by monitoring in real-time the accumulated driver's PERCLOS, i.e. proportion of time driver's eyes are closed in a 1-minute interval through non-intrusive camera(s). FPGA hardware is used as its processing platform along with Viola-Jones object detection algorithm. Viola-Jones algorithm uses Haar-like features along with AdaBoost algorithm to achieve good detection performance. 2010 Copyright SPIE - The International Society for Optical Engineering.